Object-scene semantics correlation analysis for image emotion classification - Zhou, Zibo; Zhai, Zhengjun; Chen, Huimin; Lu, Sheng (Frontiers in Neuroscience, 2025)
IntroductionImage emotion classification (IEC), which predicts human emotional perception from images, is a research highlight for its wide applications. Recently, most existing methods have focused on predicting emotions by mining semantic information. However, the “affective gap” between low-level pixels and high-level emotions constrains semantic representation and degrades model performance. It has been demonstrated in psychology that emotions can be triggered by the interaction between meaningful objects and their rich surroundings within an image. Inspired by this, we propose an Object-Scene Attention Fusion Network (OSAFN) that leverages object-level concepts and scene-level reasoning as auxiliary information for enhanced emotional classification.MethodsThe proposed OSAFN designs two different strategies to extract semantic information. Specifically, concepts are selected by utilizing an external concept extraction tool, and an Appraisal-based Chain-of-Thought (Appraisal-CoT) prompting is introduced to guide large language models in generating scene information. Next, two different attention-based modules are developed for aligning semantic features with visual features to enhance visual representations. Then, an adaptive fusion strategy is introduced for integrating the results of both the object-semantic stream and the scene-semantic stream. Additionally, a polarity-aware contrastive loss is proposed to model the hierarchical structure of emotions, improving the discrimination of fine-grained emotional categories.Results and discussionTo evaluate the effectiveness of OSAFN, we conducted numerical experiments on four affective datasets. The results demonstrate that OSAFN achieves superior performance and represents a notable contribution in the field of IEC.